CONSTRUCTION WORKERS RATING OF EXTENT OF COMPLIANCE TO TRAINING AND MOTIVATION PRACTICES IN BUILDING INDUSTRIES IN ANAMBRA STATE (NAU Journal of Technology and Vocational Education, 2024)
Building provides comfort, security, privacy and accommodation to occupant but adverse to thisis incessant building collapse that claimed lives and properties of peoples in Anambra State. Thisstudy investigated the extent of compliance to training and motivation practices in buildingindustry in Anambra State. Two research questions guided the study and two hypotheses weretested at 0.05 level of significance. A survey research design was adopted for the study. A totalof 304 out of 1,240 construction workers in building industries that were registered withMinistry of Housing Anambra State were randomly sampled. A structured questionnaire wasused to ascertain ratings of construction workers on extent of compliance to training andmotivation practices in building industry. Three experts carried out face and content validationsof the instrument. Cronbach’s alpha reliability test was used to determine the reliability of theinstrument and the results were 0.76 and 0.76 for training and motivation practices. The result ofthe reliability test yielded a value of 0.76 for the entire items which shows that the instrumenthas a high internal consistency and therefore considered suitable for the study. Mean andstandard deviation were used to answer research questions, while Analysis of Variance(ANOVA) was used to test the hypotheses. It was found out that training and motivationpractices were mostly rated to moderate extent by the construction workers. It was recommendedthat human resource managers should strictly comply to training and motivation practices inbuilding industries.
Keywords: Construction Workers, Training, Motivation and Building Industry, compliance.